Infection of Chilli by Cercospora capsici - Meon, Sariah (1990)
C. capsici was shown to be consistenlly associated with leaf spot of chilli, reducing appreciably the photosynthetic activity of infected plants leading to losses in yield. Incipient symptoms consisted of small, necrotic lesiom un the surface of the leaves, which later coalesced giving an irregular and blighted appearance with the production of abundant cOnidia, The pathogen sporulated abundantly at 20-30' but poorly at 10' C.At 40' C, no sporulation occurred. Sporulation on lesions was greatest near moisture! ,sporulation on lesions was greatest near moisture saturation but declined with decreasing water potential to -6 Mpa. The best temperature for germination was in the range of 20-30· C and declined with decreasing water potential. Pathogenicily tests and studie on the mode of infection of C, capsici on chilli leaves revealed that the fungus entered through the stomata, indicating that it was a primary invader,